Analysis of Teacher and Parent Collaboration in Learning Management to Strengthen the Character of Early Childhood: Analisis Kolaborasi Guru Dan Orang Tua Dalam Pengelolaan Pembelajaran Terhadap Penguatan Karakter Anak Usia Dini - Lina Rahayu; Nisa Aulia Sari; Wasis Wijayanto (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Strengthening the character of early childhood is important in education, but it is still hampered by suboptimal collaboration between teachers and parents. This study aims to describe the forms of collaboration, learning management, and implementation of character building in early childhood education. Qualitative research using a case study approach was conducted at the Bunga Desa PAUD in Blora Regency and the Tunas Siswa 1 PAUD in Rembang Regency through interviews, observations, and documentation analyzed using the Miles and Huberman model. The results showed that collaboration was established through intensive communication, regular meetings, WhatsApp groups, and parental involvement in school activities. Learning was managed in a planned manner through a play-based learning approach, teacher role modeling, and routine habits that instilled the values of discipline, responsibility, and independence. This study concluded that character building in early childhood will be optimal if supported by continuous collaboration between teachers and parents and the continuity of habits at school and at home.